Information Technology-Based Assessment Development Model for Rhythmic Gymnastics Referees in Semarang City (Journal of Physical Education and Sports, 2020)
This study aims to produce information technology-based products that can be used as a rhythmic gymnastic referee in processing the score of information technology-based rhythmic gymnastics matches in the city of Semarang. This research is research and development. The subject of this research is the rhythmic gymnastic referee in the city of Semarang. Data collection is done by interview survey techniques, documentation studies, and observations. The data obtained were analyzed using qualitative methods. This research produces a product in the form of a rhythmic gymnastics competition assessment application, which is a website with the address www.rhythmicgymnasticswimilia.com which can be accessed by rhythmic gymnastics referees using a smartphone or laptop. A validity test conducted by experts produces a value of 95%. This value shows that the information technology-based rhythmic gymnastics assessment model is in the very good category. So it can be concluded that the rhythmic gymnastics assessment model based on information technology can be applied in the evaluation of rhythmic gymnastics competitions.